PENGARUH MODEL EXPERIENTIAL LEARNING TERHADAP KETERAMPILAN PROSES SAINS DITINJAU DARI TINGKATAN BERPIKIR KRITIS SISWA SEKOLAH DASAR - Muliacy, Intan; Yuyu Yuliati; Mahpudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low science process skill outcomes among fourth-grade students at SDN Panyingkiran 1. The study aimed to determine the effect of the experiential learning model on science process skills, considering the critical thinking levels of fourth-grade students at SDN Panyingkiran 1, Majalengka Regency, during the 2025/2026 academic year. A quasi-experimental method with a 2 × 2 factorial design was employed. The sample consisted of 48 students divided into two groups: an experimental class using the experiential learning model and a control class using the direct instruction model. Non-probability sampling specifically purposive sampling was used to select the participants. Data were collected using science process skills tests and critical thinking tests, and were analyzed using an independent sample t-test and two-way anova. The results revealed that (1) there was a significant difference in science process skills between the experimental and control classes; (2) there was a significant difference in science process skills between students with high and low critical thinking levels; and (3) there was no significant interaction between the learning model and critical thinking levels regarding students' science process skills. The findings indicate that the experiential learning model influences students' science process skills, regardless of whether they possess high or low levels of critical thinking.